RELIGIOUS TOLERANCE IN THE OTTOMAN EMPIRE - Meirison, Meirison (Nurani, 2019)
Islam is a religion of tolerance wherever it is embraced, and the tolerant spirit will reside in the souls of the followers of this religion. Turkish people who have long embraced Islam along with the conquest carried out by Umar bin Khattab in 641 AD. The Ottoman society is a multi-ethnic and diverse religious community, Orthodox Christians, Catholics, Jews were living in peace. The question is whether religious tolerance practiced by the Ottoman Turks is in line with Islamic teachings. This qualitative discussion was carried out with a literature study. With the pattern of deduction, the author tries to make the arguments of the Qur'an and the Hadith to measure the tolerance policy implemented by the Ottoman. After the existence of a foreign capitulation agreement, the lives of minority groups are more prosperous than the Muslims. Freedom to apply the law following the teachings of each religion, tax breaks. The Jewish migration in 1877 from Kazan, Bukhara, and central Asia had flooded the Anatolian region. Minority groups such as Jews are only barred from entering the country of Hijaz (present-day Saudi Arabia) and are prohibited from establishing a Palestinian state because of a long-standing agreement since the time of the Prophet and Umar bin Khattab with Christian Palestine. Keywords: Ottoman, tolerance, Islamic religion.